Antileishmanial Activity of BNIPDaoct- and BNIPDanon-loaded Emulsomes on Leishmania infantum Parasites - Islek, Zeynep; Ucisik, Mehmet Hikmet; Keskin, Elif; Sucu, Bilgesu Onur; Gomes‐Alves, Ana G.; Tomás, Ana M.; Guzel, Mustafa; Sahin, Fikrettin (Frontiers in Nanotechnology, 2022)
Among bisnaphthalimidopropyl derivatives (BNIP), BNIPDaoct and BNIPDanon, recently came forward with antileishmanial activities beyond the standard, commercialized antileishmanial therapies. However, high-level toxicity on macrophages plus poor aqueous solubility and poor bioavailability of the compounds limit their application in therapies. Addressing these limitations, the present study introduces BNIPDaoct- and BNIPDanon-loaded emulsomes as lipid-based nanocarrier systems. Accordingly, emulsome formulations were prepared with the presence of BNIP compounds. The average diameters of BNIPDaoct- and BNIPDanon-loaded emulsomes were found as 363.1 and 337.4 nm, respectively; while empty emulsomes differed with a smaller average particle diameter, i.e. 239.1 nm. All formulations exhibited negative zeta potential value. The formulations achieved encapsulation of BNIPDaoct and BNIPDanon at around 0.31 mg/mL (501 µM) and 0.24 mg/mL (387 µM), respectively. Delivery of BNIP within the emulsomes improved the antileishmanial activity of the compounds. BNIPDaoct-loaded emulsome with IC50 value of 0.59 ± 0.08 µM was in particular effective against Leishmania infantum promastigotes compared to free BNIPDaoct (0.84 ± 0.09 µM) free BNIPDanon (1.85 ± 0.01 µM), and BNIPDanon-loaded emulsome (1.73 ± 0.02 µM). Indicated by at least ≥ 2-fold higher CC50 values, , incorporation of BNIP into emulsomes significantly reduced the toxicity of BNIPs against macrophages, corresponding to up to 16-fold improvement in selectivity index (SI) (CC50/IC50) for L. infantum promastigotes. Infection rates of macrophages were determined using dual-fluorescent flow cytometry as 68.6%. Both BNIP formulations at concentration of 1.87 µM reduced the parasitic load nearly to 40%, whereas BNIPDaoct-loaded emulosmes could further decrease the parasitic load below 20% at 7.5 µM and above. In conclusion, incorporation of BNIPDaoct and BNIPDanon into emulsomes results in water-soluble dispersed emulsome formulations that do not only successfully facilitate the delivery of BNIP compounds into the parasites and the Leishmania-infected macrophages in vitro, but also enhance antileishmanial efficacy as proven by the decline in IC50 values. The selectivity of the formulation for L. infantum parasites further contributes to the challenging safety profile of the compounds. The promising in vitro antileishmanial efficacy of BNIP-loaded emulsomes highlights the potential of the system for the future in vivo studies.